Pengaruh Inflasi Terhadap Pertumbuhan Ekonomi Indonesia Periode 2010 – 2025 - Putri Azzahra; Nursi Setiara; Busra Busra (Indo Publishing, 2026)
This study aims to analyze the effect of inflation on Indonesia's economic growth in both the short term and the long term during the period 2010–2025. The study uses quarterly data obtained from Statistics Indonesia (BPS) and Bank Indonesia. The variables used consist of inflation as the independent variable and economic growth, proxied by Gross Domestic Product (GDP), as the dependent variable. The results indicate that inflation has a negative effect on Indonesia's economic growth in both the short term and the long term. In the short term, rising inflation leads to a slowdown in economic growth due to declining purchasing power and increasing production costs. In the long term, high and unstable inflation can hinder investment and disrupt economic activities, thereby contributing to lower economic growth..